2003
DOI: 10.2208/jscej.2003.724_1
|View full text |Cite
|
Sign up to set email alerts
|

Large Scale Experiments of Buried Steel Pipelines With Elbows Subjected to Permanent Ground Deformation

Abstract: Earthquake-induced Permanent Ground Deformation (PGD) can affect significantly underground gas or water pipelines. This paper describes large-scale experiments to investigate the effect of PGD on buried steel pipelines with elbows, and to validate and calibrate Finite Element (FE) modeling. There is good agreement between both the magnitude and distribution of measured strains and deformation and those modeled with FE analyses. The analytical models are able to simulate real performance in a reliable way for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…1b), mainly for the purpose of changing direction in pipeline alignment. Interesting work on soil-pipe interaction behavior of buried pipelines with 90°elbows has been reported by Yoshizaki et al (2000Yoshizaki et al ( , 2003; a series of tests on stand-alone elbows has been reported in Yoshizaki et al (2000), followed by finite element simulations, whereas in Yoshizaki et al (2003), experiments on 100-mm-diameter 4.1-mm-thick 90°pipe elbows have been reported, also supported by finite element calculations, which employed shell elements and nonlinear springs. In a more recent publication, Suzuki et al (2014) reported experimental works on stand-alone cold-formed low-angle elbows, followed by a finite element simulation to determine numerically their bending deformation limits.…”
Section: Introductionmentioning
confidence: 99%
“…1b), mainly for the purpose of changing direction in pipeline alignment. Interesting work on soil-pipe interaction behavior of buried pipelines with 90°elbows has been reported by Yoshizaki et al (2000Yoshizaki et al ( , 2003; a series of tests on stand-alone elbows has been reported in Yoshizaki et al (2000), followed by finite element simulations, whereas in Yoshizaki et al (2003), experiments on 100-mm-diameter 4.1-mm-thick 90°pipe elbows have been reported, also supported by finite element calculations, which employed shell elements and nonlinear springs. In a more recent publication, Suzuki et al (2014) reported experimental works on stand-alone cold-formed low-angle elbows, followed by a finite element simulation to determine numerically their bending deformation limits.…”
Section: Introductionmentioning
confidence: 99%
“…During earthquakes, permanent ground deformation (PGD) can damage buried pipelines. Recent earthquakes, including the 1999 Kocaeli and Duzce earthquakes in Turkey, and the 1999 Chi-chi earthquake in Taiwan, have provided evidence of the importance of liquefaction, fault rupture, and landslides through their effects on a variety of highway, electrical, gas, and water supply lifelines [2].…”
Section: Introductionmentioning
confidence: 99%